Art of the Twenties (New York : The Museum of Modern Art, 1979)
Arp, Jean ; Atget, Eugène ; Barlach, Ernst ; Baumeister, Willi ; Bayer, Herbert ; Beckmann, Max ; Belling, Rudolf ; Bellows, George Wesley ; Blume, Peter ; Braque, Georges ; Brockmann, Gottfried ; etc.
Art of the Twenties, The Museum of Modern Art, New York, 1979
boek